2017
DOI: 10.1007/s00436-017-5627-3
|View full text |Cite
|
Sign up to set email alerts
|

The genetic diversity of metronidazole susceptibility in Trichomonas vaginalis clinical isolates in an Egyptian population

Abstract: Trichomoniasis is the most common curable sexually transmitted disease worldwide. Resistance to metronidazole in treating trichomoniasis is a problematic health issue. We aimed to determine the minimum lethal concentration (MLC) of metronidazole for Trichomonas vaginalis isolates detected in Mansoura, Egypt and studied the genotypic profile of these isolates. Vaginal swab specimens were obtained from 320 symptomatic and 100 asymptomatic females, for whom clinical examination, vaginal discharge wet mount, Giems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…In the present study, none of the clinical isolates exhibited resistance to MTZ under aerobic or anaerobic conditions with MIC <25.0 µg/ml and <6.3 µg/ml, respectively. These results conform with most reports from Egypt and other countries, where majority of clinical isolates were susceptible to MTZ with few resistant strains from USA, Europe and Africa [25,43,47,48] . It is worth mentioning that, in the present study, isolate 3 which exhibited the highest MIC of 25.0 µg/ml and 6.3 µg/ml under aerobic and anaerobic conditions, respectively, had the lowest significant growth peak of 40.5±21 after 96 h. Another study proposed different threshold concentrations of the 5-nitroimidazole drugs [47] .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, none of the clinical isolates exhibited resistance to MTZ under aerobic or anaerobic conditions with MIC <25.0 µg/ml and <6.3 µg/ml, respectively. These results conform with most reports from Egypt and other countries, where majority of clinical isolates were susceptible to MTZ with few resistant strains from USA, Europe and Africa [25,43,47,48] . It is worth mentioning that, in the present study, isolate 3 which exhibited the highest MIC of 25.0 µg/ml and 6.3 µg/ml under aerobic and anaerobic conditions, respectively, had the lowest significant growth peak of 40.5±21 after 96 h. Another study proposed different threshold concentrations of the 5-nitroimidazole drugs [47] .…”
Section: Discussionsupporting
confidence: 91%
“…Also, while studying the genetic diversity of MTZ susceptibility in 49 T. vaginalis clinical isolates of Egyptian females in Mansoura, mild resistance was observed in two isolates with MLCs of 64 μg/ml, and mild to moderate resistance in an additional two isolates with MLCs of 128 μg/ml. The four isolates displayed a unique genotype band pattern by RFLP compared to the other 45 samples that were MTZ sensitive at MIC of 1.0 μg/ml [48] . Other studies that employed RAPD technique showed a correlation between genetic relatedness of strains and similarity in their susceptibility to MTZ in vitro [54][55][56] .…”
Section: Discussionmentioning
confidence: 91%
“…In Egypt, trichomoniasis was reported by many authors (El-Sherbini et al, 2009;Kamal et al, 2015;Abdel-Magied et al, 2017;Elwakil et al, 2017). T. vaginalis infected females were presented with clinical symptoms ranged between asymptomatic to acute or chronic infections (Sherrard et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In South Africa, metronidazole resistance was reported in 6% of T. vaginalis strains isolated from women attending an antiretroviral clinic (Rukasha et al 2013 ). A study conducted by Abdel-Magied et al (Abdel-Magied et al 2017 ) reported a prevalence of 8.2% for metronidazole resistance in non-pregnant women from Egypt. This study builds on the data by Mabaso et al ( 2020 ) who have reported on metronidazole resistance in pregnant women, and now the current study shows the association between resistance profiles and prevalent genotypes.…”
Section: Discussionmentioning
confidence: 99%